Just algebra!

Algebra Level 4

If x = 2020 x=-2020 . What can we say about the number y 3 + y 2 + y , y^3+y^2+y, where

y = 1 6 ( 2 2 3 3 81 x 2 42 x + 9 27 x + 7 3 4 2 3 3 81 x 2 42 x + 9 27 x + 7 3 2 ) ? \small y=\frac{1}{6}\left(2^{\frac{2}{3}}\sqrt[3]{3\sqrt{81x^2-42x+9}-27x+7} -\frac{4\sqrt[3]{2}}{\sqrt[3]{3\sqrt{81x^2-42x+9}-27x+7}}-2\right)?

Note Try to do it without using calculators.

y 3 + y 2 + y y^3+y^2+y is real and in the interval [ 0 , 1000 ) [0, 1000) y 3 + y 2 + y y^3+y^2+y is real and in the interval [ 3000 , ) [3000, \infty) y 3 + y 2 + y y^3+y^2+y is a non real complex number y 3 + y 2 + y y^3+y^2+y is real and in the interval [ 1000 , 2000 ) [1000, 2000) y 3 + y 2 + y y^3+y^2+y is real and y < 0 y<0 y 3 + y 2 + y y^3+y^2+y is real and in the interval [ 2000 , 3000 ) [2000, 3000)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Arturo Presa
Dec 13, 2020

Define u = 3 81 x 2 42 x + 9 3 u= 3\sqrt[3]{81x^2-42x+9} and v = 27 x 7. v=27x-7. It is easy to see that ( u v ) ( u + v ) = 32. ( ) (u-v)(u+v)=32. (*)

Then we can write the number y y in the form y = 1 6 ( 2 2 / 3 u v 3 4 2 3 u v 3 2 ) . y=\frac{1}{6}(2^{2/3} \sqrt[3]{u-v}-\frac{4\sqrt[3]{2}}{\sqrt[3]{u-v}}-2). Then y + 1 3 = 1 6 ( 2 2 / 3 u v 3 4 2 3 u v 3 ) . y+\frac{1}{3}=\frac{1}{6}(2^{2/3} \sqrt[3]{u-v}-\frac{4\sqrt[3]{2}}{\sqrt[3]{u-v}}). Multiplying the term 4 2 3 u v 3 \large\frac{4\sqrt[3]{2}}{\sqrt[3]{u-v}} by u + v 3 u + v 3 , \large\frac{\sqrt[3]{u+v}}{\sqrt[3]{u+v}}, and using the property (*) to simplify we get y + 1 3 = 1 6 ( 2 2 / 3 u v 3 2 2 / 3 u + v 3 ) = 2 2 / 3 6 ( u v 3 u + v 3 ) y+\frac{1}{3}=\frac{1}{6}(2^{2/3} \sqrt[3]{u-v}- 2^{2/3}{\sqrt[3]{u+v}})=\frac{2^{2/3}}{6} (\sqrt[3]{u-v}- {\sqrt[3]{u+v}}) Raise both sides of the last equation to the third power and simplify. Then you get ( y + 1 3 ) 3 = x + 7 27 2 3 ( y + 1 3 ) (y+\frac{1}{3})^3=-x+\frac{7}{27}-\frac{2}{3}(y+\frac{1}{3}) Or, equivalently ( y + 1 3 ) 3 + 2 3 ( y + 1 3 ) = x + 7 27 (y+\frac{1}{3})^3+\frac{2}{3}(y+\frac{1}{3})=-x+\frac{7}{27} Expanding the left side and combining like terms we get, y 3 + y 2 + y + 7 27 = x + 7 27 y^3+y^2+y+\frac{7}{27}=-x+\frac{7}{27} Hence, y 3 + y 2 + y = x = 2020 y^3+y^2+y=-x=2020 and, therefore, y 3 + y 2 + y y^3+y^2+y is a real number in the interval [ 2000 , 3000 ) . [2000, 3000).

Pi Han Goh
Dec 14, 2020

Let z = 3 81 x 2 42 x + 9 27 x + 7 z = 3\sqrt{81x^2 - 42x + 9} - 27x + 7 . Rearranging gives ( z + 27 x 7 ) 2 = 9 ( 81 x 2 4 x + 9 ) ( z+27x - 7)^2= 9 (81x^2 - 4x + 9 ) . Solving for x x gives x = z 2 + 14 z + 32 54 z . x = \dfrac{-z^2 + 14z + 32}{54z} . With x = 2020 x = -2020 , we have 2020 = z 2 + 14 z + 32 54 z z 2 109094 z 32 = 0 z 32 z = 109094 -2020 = \dfrac{-z^2 + 14z + 32}{54z} \quad\implies \quad z^2 - 109094 z - 32 = 0 \quad \implies \quad z - \frac {32}z = 109094 On the other hand, we can express y y in terms of z z , y = 1 6 ( 2 2 3 z 3 4 2 3 z 3 2 ) 6 y + 2 4 3 = z 3 32 3 z 3 y = \frac16 \left ( 2^{\frac23} \sqrt[3]{z} - \frac{ 4\cdot \sqrt[3]{2} }{\sqrt[3]{z}} - 2 \right)\quad \implies \quad \dfrac{6y+2}{\sqrt[3]{4}} = \sqrt[3]{z} - \dfrac{\sqrt[3]{32}}{\sqrt[3]{z}} Cube both sides gives ( 6 y + 2 ) 3 4 = ( z 32 z ) 3 ( 6 y + 2 ) 4 3 32 3 0 ( 6 y + 2 ) 3 4 = 109094 6 ( 6 y + 2 ) 0 54 y 3 + 54 y 2 + 54 y 109080 = 0 0 y 3 + y 2 + y = 109080 54 = 2020 \begin{array} {r c l} \dfrac{(6y + 2)^3}4 &=& \left( z - \dfrac{32}z \right) - 3 \cdot \dfrac{(6y + 2)}{\sqrt[3]{4}} \cdot \sqrt[3]{32} \\ \phantom0\\ \dfrac{(6y+2)^3}4 &=& 109094 - 6(6y + 2) \\ \phantom0\\ 54y^3 + 54y^2 + 54y - 109080 &=& 0 \\ \phantom0\\ y^3 + y^2 + y &=& \dfrac{109080}{54} = \boxed{2020} \end{array}


Likewise, we can generalize this to:

If y = 1 6 ( 2 2 3 3 81 x 2 42 x + 9 27 x + 7 3 4 2 3 3 81 x 2 42 x + 9 27 x + 7 3 2 ) y=\frac{1}{6}\left(2^{\frac{2}{3}}\sqrt[3]{3\sqrt{81x^2-42x+9}-27x+7} -\frac{4\sqrt[3]{2}}{\sqrt[3]{3\sqrt{81x^2-42x+9}-27x+7}}-2\right) then y 3 + y 2 + y = x . y^3 + y^2 + y = -x .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...